2008
DOI: 10.1016/j.neuroscience.2008.08.057
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the GABAA receptor γ4-subunit gene in discrete nuclei within the zebra finch song system

Abstract: The acquisition, production and maintenance of song by oscine birds is a form of audition-dependent learning that, in many ways, resembles the process by which humans learn to speak. In songbirds, the generation of structured song is determined by the activity of two interconnected neuronal pathways (the anterior forebrain pathway and the vocal motor pathway), each of which contains a number of discrete nuclei that together form the song system. It is becoming increasingly evident that inhibitory GABAergic mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…For GABAergic receptors, the non-differential expression of the more abundant and fundamental alpha subunits of type-A receptors contrasted markedly with the differential regulation of multiple beta, delta, and epsilon subunits, suggesting these less prevalent subunits are more prominent targets of differential regulation in the song system. In particular, the up-regulation of delta subunits in all major telencephalic song nuclei, consistent with a previous report [ 70 ], suggests a distinctive feature of inhibitory neurotransmission, but its functional significance is unknown. The data on glycine receptor subunits is also intriguing, as the patterns of alpha and beta subunits seem largely complementary rather than overlapping.…”
Section: Discussionsupporting
confidence: 91%
“…For GABAergic receptors, the non-differential expression of the more abundant and fundamental alpha subunits of type-A receptors contrasted markedly with the differential regulation of multiple beta, delta, and epsilon subunits, suggesting these less prevalent subunits are more prominent targets of differential regulation in the song system. In particular, the up-regulation of delta subunits in all major telencephalic song nuclei, consistent with a previous report [ 70 ], suggests a distinctive feature of inhibitory neurotransmission, but its functional significance is unknown. The data on glycine receptor subunits is also intriguing, as the patterns of alpha and beta subunits seem largely complementary rather than overlapping.…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown that the LMAN evokes excitatory inputs in the RA via NMDA-type receptors (Mooney, 1992;Spiro et al, 1999;Sizemore and Perkel, 2008). GABA A receptor mRNA-expressing neurons and GABA-immunoreactive neurons have also been observed in the LMAN (Grisham and Arnold, 1994;Pinaud and Mello, 2007;Thode et al, 2008), although questions about whether glutamatergic and GABAergic neurons in this region interact remain unanswered. The evidence shows that the LMAN projects to area X (Vates and Nottehohm, 1995), and the RA and area X are thought to be the target nuclei of glutamatergic projection neurons.…”
Section: Vglut2 In Zebra Finchmentioning
confidence: 99%
“…Furthermore, immunohistochemical studies found that GABA is localized in somata and axon terminals in song nuclei, such as the HVC, RA, LMAN, and area X (Grisham and Arnold, 1994;Luo and Perkel, 1999;Pinaud and Mello, 2007). GABA receptors have been identified in these nuclei as well (Thode et al, 2008). Other electrophysiological studies have identified ionotropic glutamate receptors in the HVC, LMAN, RA, and caudomedial nidopallium (Mooney and Konishi, 1991;Basham et al, 1999;Pinaud et al, 2008).…”
mentioning
confidence: 99%
“…GABA A receptors have been localized in MMAN [36], so to test this idea we inactivated MMAN with GABA while recording auditory evoked activity in HVC (n = 4 in 3 birds). The effect of GABA in MMAN on auditory responses in HVC was calculated using the activity (response) during auditory stimuli (Figure 6), as the response strength was more variable, presumably due to a large variability in baseline activity.…”
Section: Resultsmentioning
confidence: 99%